Representation of Gender Equality in the “Barbie” Film: Semiotic Analysis of Roland Barthes - Dewayani, Ardya; Azwar (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This research focuses on the representation of gender equality in the live-action film